Tumor Margin Demarcation and Therapy: A NanoFlare‐Based Strategy for In Situ Tumor Margin Demarcation and Neoadjuvant Gene/Photothermal Therapy (Small 50/2018). Issue 50 (13th December 2018) - Yan, Rong; Chen, Jie; Wang, Jianhao; Rao, Jiaming; Du, Xuancheng; Liu, Yongming; Zhang, Leshuai; Qiu, Lin; Liu, Bo; Zhao, Yuan‐Di; Jiang, Pengju; Chen, Chunying; et al.
Abstract : In article number1802745, Yong‐Qiang Li and co‐workers report a robust tumor microenvironment‐responsive theranostic nanoprobe (NanoFlare). By virtue of its anisotropic oligonucleotides‐spike nanostructure, the NanoFlare can enter tumor cells universally regardless of cell type and produce a redox‐activated fluorescence signal. The NanoFlare enables accurate intraoperative margin demarcation of different tumors and efficient gene/photothermal neoadjuvant therapy in vivo.